2022
DOI: 10.1186/s12865-022-00526-z
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of dendritic cell homeostasis and Type I/Type III interferon levels in convalescent COVID-19 individuals

Abstract: Background Plasmacytoid and myeloid dendritic cells play a vital role in the protection against viral infections. In COVID-19, there is an impairment of dendritic cell (DC) function and interferon secretion which has been correlated with disease severity. Results In this study, we described the frequency of DC subsets and the plasma levels of Type I (IFNα, IFNβ) and Type III Interferons (IFNλ1), IFNλ2) and IFNλ3) in seven groups of COVID-19 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…monocytes, intermediate, and nonclassical monocytes, the activation markers sCD14, CRP, sCD163, and stissue factor, DC subsets plasmacytoid dendritic cell, myeloid dendritic cell, and IFNα, IFNβ, IFNλ1, IFNλ2, and IFNλ3, and neutrophil granular proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), and proteinase-3, and memory B cell subsets in convalescent COVID-19 individuals. [24][25][26][27][28] Our current study reveals that elderly individuals are associated with an enhanced immune and inflammatory response compared to children even during convalescence suggesting that the elderly might be prone to long-term sequelae from COVID-19. These findings will have ramifications in terms of the severity and incidence of long COVID-19 in the elderly compared to children.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…monocytes, intermediate, and nonclassical monocytes, the activation markers sCD14, CRP, sCD163, and stissue factor, DC subsets plasmacytoid dendritic cell, myeloid dendritic cell, and IFNα, IFNβ, IFNλ1, IFNλ2, and IFNλ3, and neutrophil granular proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), and proteinase-3, and memory B cell subsets in convalescent COVID-19 individuals. [24][25][26][27][28] Our current study reveals that elderly individuals are associated with an enhanced immune and inflammatory response compared to children even during convalescence suggesting that the elderly might be prone to long-term sequelae from COVID-19. These findings will have ramifications in terms of the severity and incidence of long COVID-19 in the elderly compared to children.…”
Section: Discussionmentioning
confidence: 65%
“…Our study also extends the findings to the stage of convalescence. We have previously shown that convalescent adults are characterized by alterations in alterations in lymphocyte counts, neutrophil counts, NL ratio, monocyte counts, memory T cell subset frequencies, common γ‐chain cytokines, frequencies of classical monocytes, intermediate, and nonclassical monocytes, the activation markers sCD14, CRP, sCD163, and stissue factor, DC subsets plasmacytoid dendritic cell, myeloid dendritic cell, and IFNα, IFNβ, IFNλ1, IFNλ2, and IFNλ3, and neutrophil granular proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), and proteinase‐3, and memory B cell subsets in convalescent COVID‐19 individuals 24–28 . Our current study reveals that elderly individuals are associated with an enhanced immune and inflammatory response compared to children even during convalescence suggesting that the elderly might be prone to long‐term sequelae from COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…reported that IRF7-deficient patients are prone to severe respiratory viral infections, with influenza and COVID-19, due to impaired type I and III IFN expression in both pDCs and respiratory epithelial cells ( 133 135 ). Patients with severe COVID-19 at early time points show decreased levels of type I and III IFN ( 136 ). TLR3- and TLR7-dependent production of IFN-I by pDCs and respiratory epithelial cells is essential for host defense against SARS-CoV-2 ( 137 ).…”
Section: The Function Of Irf7mentioning
confidence: 99%
“…On the one hand, IRF7 is protective against viral infection. Campbell TM et al reported that IRF7-deficient patients are prone to severe respiratory viral infections, with influenza and COVID-19, due to impaired type I and III IFN expression in both pDCs and respiratory epithelial cells (133)(134)(135). Patients with severe COVID-19 at early time points show decreased levels of type I and III IFN (136).…”
Section: Irf7 and Covid-19mentioning
confidence: 99%